Edible Landscaping Using the Nine Florida-Friendly Landscaping™ Principles - Tiare Silvasy; Lynn Barber; Esen Momol; Tina McIntyre; Tom Wichman; Gail Hansen; Jen Marvin; Terra Freeman; Joseph Sewards; Wendy Wilber; Jacqlyn Rivas (EDIS)
Maintaining edible landscapes in a way that protects the environment is an important concern for protecting Florida’s water quality. The objective of this new 7-page publication of the UF/IFAS Environmental Horticulture Department is to introduce the framework of the Florida-Friendly Landscaping™ principles and apply the principles to guide decisions about Best Management Practices (BMPs) for care of edible landscapes. Written by Tiare Silvasy, Lynn Barber, Esen Momol, Tina McIntyre, Tom Wichman, Gail Hansen, Jen Marvin, Terra Freeman, Joseph Sewards, Wendy Wilber, and Jacqlyn Rivas. https://edis.ifas.ufl.edu/ep594